2012
DOI: 10.1038/npp.2011.337
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of Social Influence by Methylphenidate

Abstract: The ability to infer value from the reactions of other people is a common and essential ability with a poorly understood neurobiology. Commonly, social learning matches one's values and behavior to what is perceived as normal for one's social group. This is known as conformity. Conformity of value correlates with neural activity shared by cognitions that depend on optimum catecholamine levels, but catecholamine involvement in conformity has not been tested empirically. Methylphenidate (MPH) is an indirect dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 71 publications
(109 reference statements)
2
44
0
Order By: Relevance
“…Previous research has demonstrated that enhancement of dopamine responses by direct administration of a dopamine and noradrenalin agonist (methylphenidate) facilitates the conformity effect [10]. The present study extended this finding by demonstrating that DRD3 , an important player within the dopaminergic system, is associated with individual differences in conforming behavior.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Previous research has demonstrated that enhancement of dopamine responses by direct administration of a dopamine and noradrenalin agonist (methylphenidate) facilitates the conformity effect [10]. The present study extended this finding by demonstrating that DRD3 , an important player within the dopaminergic system, is associated with individual differences in conforming behavior.…”
Section: Discussionsupporting
confidence: 80%
“…The increased reward-related dopamine activity is assumed to reflect the amplification of phasic dopamine responses to appetitive stimuli [22]. Methylphenidate, a drug that amplifies the dopamine response to appetitive stimuli [43], has been shown to increase conforming behavior after moderate social conflict [10]. The authors suggested that the enhanced dopamine response increases the magnitude of the incentive salience of agreeing with others [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations